Not getting laid: consumer acceptance of precision fermentation made egg - Zollman Thomas, Oscar; Chong, Mark; Leung, Angela; Fernandez, Tricia Marjorie; Ng, Shu Tian (Frontiers in Sustainable Food Systems, 2023)
Mounting concern over the negative externalities of industrialised animal agriculture, coupled with falling costs curves of novel food technologies have birthed the field of cellular agriculture: a new category of food technology seeking reproduce the experiences of animal protein, promising a cleaner, more ethical way of enjoying animal proteins. This research examines consumer acceptance of precision-fermentation (PF) made egg products in Germany, Singapore, and the USA. Using an online survey of 3006 participants, the study examines demographic and dietary traits that predict willingness to try such products and identifies the reasons why consumers are most attracted to them. The findings suggest that precision-fermentation made egg products are likely to find a willing market, with a substantial proportion (48-57%) of participants willing to try the product, with vegetarians and vegans displaying the highest enthusiasm. Egg consumption habits and, to a lesser extent, income also predict acceptance. Major reasons considered for adopting the product were animal welfare in Germany, and health aspects in Singapore and the USA, as well as a strong draw for curiosity in all three countries. Observed differences between the acceptance of PF egg and PF dairy are discussed, as well as comparisons to existing alternative protein product adoption.